Panggung Budaya, Jendela Mazhab: Peran Islamic Cultural Center Jakarta dalam Memperkenalkan Syiah di Indonesia - Dhimas Pandapotan Sipahutar (Inklusiva: Jurnal Studi Agama-Agama, 2023)
This paper examines the role of the Islamic Cultural Center (ICC) Jakarta as a cultural platform for the introduction of Shia Islam in Indonesia, particularly in the Greater Jakarta area. ICC functions as an intellectual hub for the Shia community, focusing on studies of Islamic culture and serving as a form of Iranian cultural diplomacy in the country. Rather than conducting direct propagation of Shia teachings, ICC adopts a cultural approach aimed at fostering understanding and correcting negative prejudices about Shia and its figures within the wider society. Through religious and cultural programs, seminars, scholarly discussions, publishing, educational activities, and the use of information technology, ICC actively contributes to promoting Islam as a religion of mercy for the universe (rahmatan lil ‘alamin) and serves as a bridge for inter-sectarian communication. This research employs a qualitative method, utilizing interviews, field observations, and literature studies, analyzed through an anthropological lens based on Bronislaw Malinowski’s functionalism theory. The results highlight that ICC Jakarta prioritizes educational and cultural endeavors in introducing the Shia identity to Indonesia’s diverse society.